Sustainable development of small business in Kazakhstan - Venera Zarubina; Mikhail Zarubin; Zhaukhar Yessenkulova; Tursyngul Gumarova; Almira Daulbayeva; Zhuldyz Meimankulova; Aizhan Kurmangalieva (Economies, 2024)
The small business sector in Kazakhstan demonstrates dynamic growth, but its sustainable development in modern conditions requires activation from government agencies, society and entrepreneurs themselves. The purpose of the article was to study the development of small entrepreneurship in Kazakhstan and develop a mechanism for sustainable development based on network interaction 'business entities-society-state' with the identification of priority areas of development based on a rating approach. The methods of bibliographic analysis of scientific literature, statistical, correlation analysis, survey, comparative analysis and ranking based on data normalization were used. The results revealed the need to formalize indicators of sustainable development of the small business sector in strategic development programs; create conditions, support, explain the importance and prospects of investing in sustainable innovations by small businesses and form a balanced strategy for achieving carbon neutrality based on network interaction 'business entities-society-state' with the identification of priority areas of development based on a rating approach to ensure transparency and publicity of decisions made. Conclusions were made about the need to popularize sustainable development among business entities, stimulate investment activity through government participation, enact legislative regulation of public presentation of non-financial reporting, and assist society in the formation of an ESG culture.
Keywords: 330; ESG; Kazakhstan; network interaction “business entities–society–state”; responsible investment; small business; sustainable development